Strategi Adaptasi: Kisah Desa Kawa dan Desa Morodemak dalam Menghadapi Perubahan Populasi dan Ekologi - Widhyanto Muttaqien (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2018)
Population growth in coastal areas, especially as a result of migration, has put pressure on the environment, both the built environment and the community management environment in implementing sustainable livelihood strategies. This paper wishes to explain two models of community adaptation in two distinct areas, namely Morodemak Village on the north coast of Central Java, which began to recede in the management of common resources, and Kawa Village in Seram Barat coast, which is still strong in maintaining the tradition of coastal and terrestrial territorial management as a common resource. The research methodology used in this research is qualitative approach, with semi structured interview and focus group discussion. From the results of the study, it was revealed that people were able to reshape their resources based on ecological and social changes, as their adaptation strategy in sustaining sustainable livelihoods.